Ageism and nursing students, past or reality?: A systematic review. (March 2023) - Allué-Sierra, Leticia; Antón-Solanas, Isabel; Rodríguez-Roca, Beatriz; Anguas-Gracia, Ana; Echániz-Serrano, Emmanuel; Fernández-Rodrigo, María Teresa; Navas-Ferrer, Carlos; Subirón-Valera, Ana Belén; Urcola-Pardo, Fernando; Satústegui-Dordá, Pedro J.
Abstract: Objective: This systematic review aimed to summarise and update existing knowledge about ageism among nursing students through the following research question: what is the perception and attitudes of ageism among student nurses? Design: A systematic review of longitudinal and cross-sectional studies of ageism in nursing students was carried out. Data sources: The literature search was conducted in the scientific databases Pubmed and Scopus in February 2021. Review methods: After the screening process, 22 studies meeting the selection criteria were selected; 8 more were identified after manually searching the selected paper' reference lists. A total of 30 studies were included in the review. The JBI Critical Appraisal Checklists for Analytical Cross-Sectional studies and for Cohort Studies were used to appraise the articles' quality. Results: There was large variability in the manifestation of ageism among student nurses, as well as in the instruments used for assessment. Most of the articles analysed attitudes towards old age, the majority of which were positive. Being a female student, being on the final year of study and having regular contact or cohabitation with an older adult were three of the main determinants in the expression of positive attitudes towards the elderly. Conclusions: Our findings suggest that student nurses generally have positive attitudes towards old age, although ageist beliefs and discriminatory behaviours were identified and should be studied in greater depth. Training programs for future care professionals have a responsibility to educate from a non-stereotypical perspective based on current societal needs. Highlights: Ageism, although less strongly, is still present among nursing students. Medical Ageism harms in one way or another the patients who suffer from it. Education in Gerontology and intergenerational contact are possible solutions to ageism.